A virtual promise of happiness: kinship on the websites of Danish fertility clinics and sperm banks. Issue 8 (17th November 2019) - Harrison, Katherine
ABSTRACT: Each month thousands of people travel across national borders to access assisted reproductive treatments across Europe. The possibility to purchase fertility treatments in a similar way to other products and services has led not only to a clearly defined market place and customer, but has also contributed to scholarly work on critical studies of kinship. To date, however, there has been little research enquiring into how new media technologies relied upon by parents for finding fertility information may contribute to shaping and circulating ideas of kinship. Within the transnational fertility marketplace, Denmark has become a hub for would-be parents due to liberal legislation, cheaper prices and shorter waiting times. As the first contact point for potential fertility travellers, the websites of Danish fertility clinics and sperm banks fulfil several roles, including marketing, disseminating information about scientific breakthroughs, and providing guidance on healthy lifestyle choices for potential parents. Using multimodal analysis of home pages, this paper examines how the websites of Danish fertility clinics and sperm banks contribute to shaping and circulating ideas about kinship. These websites attract and engage with customers by creating emotive representations of kinship that rely on the mother-child image.